THE THE CORRELATION OF CHRONIC ENERGY DEFICIENCY (CED) WITH THE GENESIS OF ANEMIA ON PREGNANT WOMEN AT THE WORK AREA OF COMMUNITY HEALTH CENTER IN SRIMULYO SUOH OF WEST LAMPUNG REGENCY 2020: THE CORRELATION OF CHRONIC ENERGY DEFICIENCY (CED) WITH THE GENESIS OF ANEMIA ON PREGNANT WOMEN AT THE WORK AREA OF COMMUNITY HEALTH CENTER IN SRIMULYO SUOH OF WEST LAMPUNG REGENCY 2020 - Kurniasih; Iis Tri Utami; Fitriana; Linda Puspita (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2021)
The prevalence of anemia on pregnant women in Indonesia is 37.1%. The genesis of anemia on pregnant women about 20% up to 89% by setting 11 grams as the basis. The problem of malnutrition on pregnant women is still a concernmajor, these problems include anemia and pregnant women with Chronic Energy Deficiency (CED). This research was to determine the correlation of chronic energy deficiency (CED) with the genesis of anemia on pregnant women at the work area of community health center in SrimulyoSuoh of West Lampung Regency 2020. The research type is quantitative with Case Control research design. The population in this research were all pregnant women on third trimester at the work area of community health center in SrimulyoSuoh of West Lampung Regency in 2020amount to 145 people with 39 cases of anemia, while the sample in this research with a ratio of 1:1, so the number of samples used 39 pregnant women with anemia and 39 pregnant women without anemia so the sample numbered 78 respondents by using purposive sampling technique. The research results are there is correlation of chronic energy deficiency (CED) with the genesis of anemia on pregnant women at the work area of community health center in SrimulyoSuoh of West Lampung Regency 2020 with (P value 0.041 and OR 2.86). Suggestions for the society, especially for pregnant women, namely the needs to increase knowledge through participation in health education and classes for pregnant women so that pregnant women improve their nutritional intake during pregnancy, and routinely visit community health center to conduct pregnancy check-up.